Corona virus disease-2019 pandemic: Ensuring delivery of essential HIV services - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Wolters Kluwer Medknow Publications, 2020)
The corona virus disease-2019 (COVID-19) pandemic has been reported among all the age-groups, with severity being highest among elderly people and those with some pre-existing illnesses. The available evidence has not suggested that a person living with HIV (PLHIV) has a higher risk of acquisition of infection or the development of serious complications if they do get infected with COVID-19, provided their immune system is not compromised. Amidst dealing with this COVID-19 emergency, it is quite possible that delivery of essential health services, including those required for PLHIV will be temporarily interrupted. In these times of emergency, we should aim for reducing the number of visits to the ART center and inform them about the disease. In conclusion, the COVID-19 pandemic is bound to impact the delivery of essential services for PLHIVs and thus it is our utmost responsibility to improve the resilience of the health system to ensure that appropriate strategies are adopted to ensure the uninterrupted supply of the essential services are offered to these vulnerable population groups.